Mapping the Evolution of Engineering Design Thinking: A Systematic Review and Bibliometric Analysis of Scopus Publications (2020 – 2025) - Eva Rahayu Putri; Dewanto Harjunowibowo; Sri Budiawanti (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
Engineering Design Thinking (EDT) has become a critical framework in contemporary engineering education by integrating creativity, human-centered perspectives, and systems thinking to address complex problems. This study aims to map the evolution of EDT research, identify dominant thematic structures, and indicate future research directions through a hybrid approach combining a Systematic Literature Review (SLR) and Bibliometric Analysis. Using the Scopus database, 893 publications published between 2020 and 2025 were analyzed following the PRISMA protocol and VOSviewer was used to visualize co-authorship, citation, and keyword networks. The results reveal a substantial increase in EDT-related publications after 2015, with the United States, China, and Indonesia emerging as leading contributors, indicating a growing global research landscape. Thematic analysis identifies five core and interrelated dimensions of EDT: technology integration, collaboration and communication, ideation and creativity, human-centered design, and systems and sustainability thinking. Despite this growth, empirical investigations and cross-regional collaborations remain limited. By integrating systematic and large-scale bibliometric perspectives and contextualizing recent studies within a broader historical trajectory (1957–2025), this research provides the first comprehensive mapping of EDT’s intellectual development and offers a unified conceptual model to guide future research and educational practice